WEB BASED RAIN GAUGE CALIBRATOR - Sensus Wijonarko; Tatik Maftukhah; Dadang Rustandi; Bernadus Sirenden; Nur Tjahyo Darmayanti (LIPI Press, Anggota IKAPI, 2019)
Rain gauges in Indonesia need recalibration at least twice a year, viz. at the end of dry season where the rain gauges will soon work harder and at the end of rainy season where usually there are many garbage on each rain gauge orifice. Based on the direct surveys in the fields and discussions at some rain gauge calibration laboratories in Indonesian western, central, and eastern parts, the calibration officers in the visited offices generally used manual rain gauge calibrators to recalibrate rain gauges on their fields. Therefore, the dependency of calibration results to the human beings is very high. Meanwhile to avoid data gathering discontinuation, rain gauges should be recalibrated in situ. To cope with this problem and other issues related to rain gauge calibrators, a research to develop a web based rain gauge calibrator was carried out. The research result using research and development method showed that this calibrator can work well as an in situ and ex situ rain gauge calibrator.